2003
DOI: 10.1097/01.pcc.0000074260.93430.6a
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear analysis of heart rate variability during propofol anesthesia for short-duration procedures in children

Abstract: We conclude that power spectral analysis of heart rate variability may be an accurate and clinically useful measure of depth of propofol anesthesia. We speculate that high-frequency heart rate power during propofol anesthesia correlates with depth of anesthesia, whereas low-frequency power allows for assessment of the patient's sympathetic response to pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 46 publications
1
14
0
2
Order By: Relevance
“…Toweill et al . speculated that HF correlates with depth of anesthesia during propofol anesthesia, whereas LF allows for the assessment of the sympathetic response to pain in children with propofol anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toweill et al . speculated that HF correlates with depth of anesthesia during propofol anesthesia, whereas LF allows for the assessment of the sympathetic response to pain in children with propofol anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the balance of the autonomic nervous activity might play a significant role in the determination of the HR response to endotracheal intubation. Toweill et al (12) speculated that HF correlates with depth of anesthesia during propofol anesthesia, whereas LF allows for the assessment of the sympathetic response to pain in children with propofol anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Despite nonspecific pathophysiological mechanisms, there is ample evidence that the frequency contributions to HRV are altered in illness states, and that the degree of alteration correlates with illness severity. It is illustrative that alterations in the spectral HRV analysis related to illness severity have been demonstrated from hypovolaemia [49] to heart failure [50-52], from hypertension [53,54] to coronary artery disease [55,56], and from angina [57] to myocardial infarction [58], in addition to chronic renal failure [59], autonomic neuropathy secondary to diabetes mellitus [60], depth of anaesthesia [61] and more. Spectral analysis of HRV has been applied in the ICU.…”
Section: Frequency Domain Analysismentioning
confidence: 99%
“…A study concluded the power spectral analysis of heart rate variability may be a practical use for measuring DoA [9]. Horiguchi and Nishikawa evaluated studies of anesthesia based on monitoring the heart rate with the drug propofol [10, 11].…”
Section: Introductionmentioning
confidence: 99%